Comparative validity of three simulation platforms for objective assessment of otoscopy skills. (20th January 2023) - Rotimi, Oloruntobi; Haymes, Adam; Dodds, Isobel; Bhutta, Mahmood
Abstract: Objectives: To assess the face, construct and content validity of three different platforms for otoscopy skills assessment, using a traditional otoscope with manikin, digital otoscope (Tympahealth) with manikin, and traditional otoscope with a low‐cost model ear (SimEar). Design: Prospective mixed methods study. Setting: Tertiary hospital. Participants: Postgraduate trainees and expert assessors. Main Outcome Measures: Face and Content validity based on expert assessor ranking on each model and their feedback from semi‐structured interviews. Construct validity based on Objective Structured Clinical Examination scores. Results: Each platform differed in face, construct and content validity scores, with no one platform consistently outperforming others. Three main themes were identified during thematic analysis of expert assessor interviews: ability to assess what is seen, anatomical reality, and ease of use. The low‐cost model showed greatest potential, where modification to include a silicone ear could lead to high validity with marginal increase in cost. Conclusion: Several modalities for assessing otoscopy skills exist, each with advantages and disadvantages. Modifications to a low‐cost model, for use with either a traditional or digital otoscope, could prove to be the best model.